New data about the shark fauna of the Brejo Santo formation, Late Jurassic of the Araripe Basin, Northeastern Brazil. (March 2023) - Batista, T.A.; Gallo, V.; Bantim, R.A.M.; Sena, M.V.A.; Santos Filho, E.B.; De Lima, F.J.; Saraiva, A.A.F.; Silva, J.L.; Lima, M.J.F.; Oliveira, G.R.
Abstract: The Late Jurassic fauna of the Araripe Basin is represented by chondrichthyans and osteichthyans (Actinopterygii and Sarcopterygii). At the present study, we describe new records of hybodontid shark from the Brejo Santo Formation (Upper Jurassic – Tithonian) and characterize their paleohistology. They are represented by a complete cephalic spine of Planohybodus sp., which indicates sexual dimorphism, being present only in male sharks; as well as by a dorsal spine, which is the most complete found so far for this formation. Microstructural analyzes were performed in the dorsal spine, indicating this specimen as a juvenile, early sub-adult individual, approximately one year old. Highlights: New specimens of Chondrichthyes Fauna from the Brejo Santo Formation. First ontogenetic data through histological analysis on shark spines in the Araripe Basin. New data about the Jurassic shark fauna of South America.